2019
DOI: 10.3389/fmicb.2019.00339
|View full text |Cite
|
Sign up to set email alerts
|

RelQ Mediates the Expression of β-Lactam Resistance in Methicillin-Resistant Staphylococcus aureus

Abstract: An induced stringent response, which is established by an increased level of (p)ppGpp, is required for the expression of β-lactam resistance in methicillin-resistant Staphylococcus aureus (MRSA). However, it is not clear whether RSH (enzyme mediating stringent response to amino acid starvation) or small alarmone synthetases (SASs) are involved in the maintenance of (p)ppGpp level in response to β-lactams. Since the S. aureus genome encodes two active SASs (RelP and RelQ), their contribution to the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…The stringent response is a mechanism that regulates the expression of several genes by the synthesis of the alarmone (p) ppGpp and is induced by nutrient starvation and various environmental stresses. 42 Our results conrmed that RelQ, an enzyme involved in the stringent response, was overproduced in oxacillin-treated MRSA and are consistent with previous studies that oxacillin induces RelQ expression ( Fig. S4 †).…”
Section: Stringent Responsesupporting
confidence: 93%
See 1 more Smart Citation
“…The stringent response is a mechanism that regulates the expression of several genes by the synthesis of the alarmone (p) ppGpp and is induced by nutrient starvation and various environmental stresses. 42 Our results conrmed that RelQ, an enzyme involved in the stringent response, was overproduced in oxacillin-treated MRSA and are consistent with previous studies that oxacillin induces RelQ expression ( Fig. S4 †).…”
Section: Stringent Responsesupporting
confidence: 93%
“…43 Among these proteins, RelQ was found to play a major role in mecA gene expression in the deletion mutant model, and an increase in blactam resistance was observed in the overexpression model of this protein. 42 Therefore, our results show that the b-lactam resistance of MRSA is strongly associated with the stringent response mediated by RelQ. Fig.…”
Section: Stringent Responsementioning
confidence: 55%
“…However, recent reports have suggested that there may be differences in the respective levels of induction (physiological roles) of relP and relQ in methicillin resistant versus methicillin susceptible S . aureus strains in response to treatment with beta-lactam antibiotics; and that RelQ may play a more important role in (p)ppGpp production and related beta-lactam resistance mechanisms than was previously thought [90, 91]. In E .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Rel, Firmicutes express one or two short/small (p)ppGpp synthetases (SASs), termed RelP and RelQ (known as YjbM and YwaC, respectively, in Bacillus subtilis ) ( Atkinson et al, 2011 ). All SASs appear to be primarily involved in maintainence of basal (p)ppGpp pools during growth, though have been also linked to a timely activation of the SR ( Gaca et al, 2012 ) and to cell envelope stress tolerance ( Geiger et al, 2014 ; Bhawini et al, 2019 ). While the majority of Firmicutes encode both RelP and RelQ, few species including Streptococcus pneumoniae , Streptococcus suis and all members of the Enterococcus genus only encode RelQ ( Atkinson et al, 2011 ).…”
Section: Gram-positive Pathogensmentioning
confidence: 99%
“…In another study, the relP Sa and relQ Sa genes were shown to be strongly induced upon treatment with cell wall-active antibiotics (ampicillin and vancomycin) and simultaneous inactivation of both genes significantly decreased tolerance of S. aureus toward these antibiotics ( Geiger et al, 2014 ). In a more recent study, the association of SASs with antibiotic tolerance was traced to RelQ as inactivation of relQ Sa decreased tolerance to β-lactam antibiotics in methicillin-resistant S. aureus (MRSA) by interfering with mecA gene expression, which codes for an alternative penicillin-binding protein ( Bhawini et al, 2019 ). Interestingly, the importance of RelQ Sa in β-lactam tolerance could be bypassed by activation of the SR with mupirocin (an isoleucine analog/ ile tRNA inhibitor that triggers the SR), suggesting that mecA transcription requires a certain (p)ppGpp threshold ( Bhawini et al, 2019 ).…”
Section: Gram-positive Pathogensmentioning
confidence: 99%